RANCANG BANGUN SISTEM PLTB MENGGUNAKAN KINCIR ANGIN TAHAN CUACA EKSTREM UNTUK OPTIMALISASI ENERGI TERBARUKAN DI KAPAL: Perancangan, Implementasi, dan Pengujian Pembangkit Listrik Tenaga Bayu (PLTB) Pada Kapal. - Shodiq Dhiyaulhaq Khosyi; Edi Kurniawan; Elly Kusumawati (JURNAL PENDIDIKAN VOKASIONAL TEKNIK ELEKTRONIKA (JVoTE), 2026)
The ever-increasing demand for electrical energy on ships drives the development of renewable energy sources as an alternative to reduce reliance on fossil fuels. This study aims to design and evaluate a prototype wind power generator utilizing an Archimedes-type wind turbine as a supplementary energy source for ship electrical systems. The research employs a Research and Development (R&D) methodology, encompassing design, prototype fabrication, and both static and dynamic testing phases. The prototype comprises an Archimedes wind turbine, a DC generator, a Solar Charge Controller (SCC), a LiFePO4 battery, an inverter, a step-down module, and an ESP32-based monitoring system. Test results indicate that the DC generator produces a maximum voltage of 13.9 V with a charging current of 17.6 mA at a rotational speed of 1,199.1 rpm. In dynamic testing, wind approaching from the front-left yielded the best performance, with a charging current of 17.7 mA and a charging voltage of 5.7 V, whereas wind from the rear produced no electrical output. Field tests demonstrated that locations free from building obstructions resulted in higher and more stable charging compared to locations obstructed by buildings. The study concludes that the Archimedes-type wind turbine has the potential to serve as a renewable energy source supporting ship electrical systems, with performance influenced by wind direction and environmental conditions.